A follow-up study of the vocational course graduates of the Pasay City High School under the 2-2 plan - Pizarro, Anita (Hans) 1922- (s.n.], 1973)
This follow-up study determined the cause of the loss of interest of Pasay City High School students on the Vocational Course which used to be popular the first time it was offered. The vocational program of the school is evaluated in this study in order to institute remedies for the welfare of the students concerned.